1994
DOI: 10.1089/end.1994.8.419
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nephrectomy Results in Better Postoperative Pulmonary Function

Abstract: The pulmonary response to nephrectomy was studied in 16 patients undergoing laparoscopic (n = 8) or open (n = 8) nephrectomy using a standardized anesthetic technique. Although there was no significant difference between the two groups at 24 hours, postoperative pulmonary function measures (P = 0.02-0.03) and oxygenation (P = 0.03) were significantly better in the laparoscopic surgery group at 48 hours. The median opiate analgesic requirement (P = 0.02) and the number of nights spent in the hospital (P = 0.003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Eden et al reported that the pulmonary function after laparoscopic nephrectomy was better than after open nephrectomy. 8 However, creating a pneumoperitoneum can cause cardiovascular changes similar to those of heart failure. 9 The increase in both systemic and pulmonary vascular resistances raises the cardiac afterload , which results in a decrease in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Eden et al reported that the pulmonary function after laparoscopic nephrectomy was better than after open nephrectomy. 8 However, creating a pneumoperitoneum can cause cardiovascular changes similar to those of heart failure. 9 The increase in both systemic and pulmonary vascular resistances raises the cardiac afterload , which results in a decrease in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Many of its benefits are the same ones that have been demonstrated for other, more common laparoscopic procedures (e.g., cholecystectomy, fundoplication, etc.) [2]. Significant advantages include shortened hospitalization, decreased morbidity, minimal analgesic requirement, rapid return to full activity, and improved cosmetic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It has not yet been possible, however, to assemble all of the available pieces in one project, and many pieces are missing altogether. 7,8 It also results in less pain, 9 shorter hospital stays, 10,11 lower hospital costs, 12 quicker return to activities of daily living, 13 improved postoperative pulmonary function, [14][15][16][17][18] and smaller incisional scars. These factors contribute to an environment in which patient safety cannot be assumed.…”
mentioning
confidence: 99%